Strategies Toward Energy Transition in Indonesia: An Assessment of Multi-Regional Biomass Supply for Coal Co-Firing Power Plants - Sugiyono, Agus; Kuncoro, Arief Heru; Fitriana, Ira; Yudiartono; Wijaya, Prima Trie; Ridlo, Rohmadi; Aminuddin; Wibowo, Edi; Hilmawan, Edi; Nurrohim, Agus (International Journal of Sustainable Energy Planning and Management, 2025)
Coal remains the dominant source of electricity generation in Indonesia, accounting for around 55% of installed capacity. As a fossil fuel, coal contributes significantly to greenhouse gas (GHG) emissions, posing a challenge to Indonesia’s commitment to the Paris Agreement. Biomass co-firing in coal power plants offers a promising pathway to reduce GHG emissions. However, sustainable biomass supply is a major challenge due to Indonesia’s archipelagic geography, which causes regional disparities in power capacity, fuel types, and biomass potential. This study assesses the potential of multi-regional biomass supply in relation to emission reduction targets, using secondary data for provincial biomass waste inventories is assessed. The Low Emissions Analysis Platform (LEAP) model projects coal demand from 2025 to 2045 under two scenarios: business as usual (BAU) and biomass co-firing (BCF) with biomass shares of 5%, 10%, and 15%. Findings show that municipal and industrial waste alone cannot sustain long-term co-firing at the national level. Therefore, multi-regional supply-demand analysis is essential. Provinces such as Riau, North Kalimantan, Central Kalimantan, West Kalimantan, Papua, Bangka Belitung Islands, and Jambi are identified as surplus regions. A 15% biomass co-firing scenario could reduce emissions by 108 Mt of CO₂ by 2045 and lower emission intensity nationwide.